Trajectories of Sexual Risk Behaviors and the Associated Factors Among Young Men Who Have Sex With Men in China - Wei, Liqing; Tian, Jiawei; Guo, Menglan; Zhu, Biao; Jiang, Qingqing; Yu, Bin; Yan, Hong (Frontiers in Public Health, 2022)
Background Young men who have sex with men (YMSM) are at high risk of HIV infection that accounts for an increasing proportion of new human immunodeficiency virus (HIV) infections in China. However, little is known about the trajectories of sexual risk behaviors in this population. The study aimed to investigate longitudinal patterns of sexual risk behaviors among YMSM in China. Methods Study data were collected from a prospective cohort study among 460 YMSM from 2017 to 2020. Based on the predicted HIV infection risk scores, distinct sexual risk behaviors trajectories of YMSM were estimated and plotted using the group-based censored normal model to identify the predictors of trajectories change over time. Results Three sexual risk behaviors trajectories were identified: a decreasing low-risk group (7.6%), an intermediate-risk group (67.4%), and an ascending high-risk group (25.0%). Compared to the decreasing low-risk group, intermediate-risk group membership was associated with being from rural areas, current smoker and higher depressive symptoms; ascending high-risk group membership was associated with an education level of high school or lower, being from rural areas, younger age at sex debut with a man, current smoker, higher depressive symptoms and sexual minority stress. Conclusions Sexual risk behaviors among YMSM changed over time within different trajectories. Identifying YMSM belonging to high-risk trajectories before HIV infection is vital for the intervention and may reduce HIV transmission.